Rapid Detection and Quantification of Rhynchosporium secalis in Barley Using a Polymerase Chain Reaction - Jozef Gubiš; Martina Hudcovicová; Marcela Gubišová (Czech Journal of Genetics and Plant Breeding, 2006)
PCR primers for diagnosis of Rhynchosporium secalis in seed samples of barley were developed. For the quantification of the pathogen in seed samples a real-time PCR with SYBR Green approach was used. Amounts from 1.8 to 419.1 pg of R. secalis DNA per 100 ng of total DNA were detected in 18 samples of barley seeds contaminated by R. secalis in field conditions. The correctness of this quantitative analysis was checked using an artificial infection of seeds with 1, 2, 5 and 20% level of infection by R. secalis. The level of contamination of artificially infected samples decreased with a lowering amount of added seed powder contaminated by the pathogen, the correlation coefficient for this analysis was 0.98. While the primer pair used in these analyses shows cross-reactions with other pathogens (P. teres, Drechslera tritici-repentis, F. culmorum and F. poe), it is recommended to check the products of RT-PCR by agarose-gel electrophoresis, in which these pathogens are easily distinguishable from R. secalis by different lengths of the amplified fragments.